Possible impacts of COVID-19 pandemic on domestic wastewater characteristics in Kuwait - Ahmed, Mohd Elmuntasir; Al-Haddad, Adel; Bualbanat, Ali (Journal of Environmental Engineering and Landscape Management, 2022)
The wastewater quality alterations due to the use of cleaning agents, sanitisers, and disinfectants, in addition to the accompanying use of water during COVID-19 have potential impacts on wastewater treatment operations. How the characteristics of wastewater could be altered by the COVID-19 pandemic was the concern of this investigation. Daily records of the Ardiya catchment in Kuwait City were examined for the period 2015–2020. Perhaps due to the excessive use of water during 2020 (446 compared to the five-year average of 436 l/c.d) and the corresponding wastewater generation increase (253 compared to the five-year average of 239 l/c.d), the effect of chemical usage on the wastewater quality has dampened. Nonetheless, an increase in the frequency of COD/BOD ratio > 3, TP in the range 6.5 to 8.5, TKN in the range 40 to 50 were observed in 2020, which was not observed during 2015–2019. These COVID-19 related alterations are important to take into consideration in wastewater treatment operations to achieve wastewater treatment targets.